Sustainable Environment and in the Context of Environment Economy Necessary and an Analyze - KENDIRLI, Selcuk; UNAL, Gunes; BASARAN, M. Sakir (Journal of Economic Development, Environment and People, 2014)
:In global world, the environment has become a scarce resource. Since economics is about how to deal with scarce resources, environment and economics are interrelated with each other. On the other hand it is also clear that economics which creates both positive and negative externalities, affects the environment. For this reason, it is not possible to except environmental problems from the economics. Today some socio-economic activities like increasing consumption based on shopping malls, urban regeneration, fast population growth and etc. have being created environmental cost. One way of using economics is to ensure that the costs and the benefits of environmental measures are well balanced. Although it is difficult to estimate costs and benefits, there is an increasing demand that this is should be done before the economical activity. Economic and environmental objectives are often perceived as being contradictory. It is believed that a choice must be made between one and the other and that cannot be achieved concurrently. To change this perception, some measures should be taken on both national and international level. At this point, an efficient environmental auditing is being important day by day to ensure environmental economics.